Generation and characterization of a rabbit monoclonal antibody site‐specific for tau O‐GlcNAcylated at serine 400. Issue 22 (7th October 2013) - Cameron, Andrew; Giacomozzi, Brandy; Joyce, John; Gray, Audrey; Graham, Danielle; Ousson, Solenne; Neny, Maud; Beher, Dirk; Carlson, George; O'Moore, Jill; Shearman, Mark; Hering, Heike
Abstract : Aggregation of tau into paired helical filaments is a pathological process leading to neurotoxicity in Alzheimer's disease and other tauopathies. Tau is posttranslationally modified by O‐linked N ‐acetylglucosamine (O‐GlcNAc), and increasing tau O‐GlcNAcylation may protect against its aggregation. Research tools to study the relationship between tau aggregation and tau O‐GlcNAcylation have not been widely available. Here we describe the generation of a rabbit monoclonal antibody specific for tau O‐GlcNAcylated at Ser400 (O‐tau(S400)). We show the utility of this antibody for in vitro and in vivo experiments to investigate the function of O‐GlcNAc modifications of tau at Ser400. Abstract : Novel antibody specific for O‐GlcNAc tau at Ser400. Utility for in vitro and in vivo samples. Low cross‐reactivity with other O‐GlcNAcylated proteins.